Fast-food consumption and body mass index in children and adolescents: an international cross-sectional study - Irene Braithwaite; Alistair W Stewart; Robert J Hancox; Richard Beasley; Rinki Murphy; Edwin A Mitchell; the ISAAC Phase Three Study Group (N Aït-Khaled, HR Anderson, MI Asher, B Björkstén, B Brunekreef, J Crane, P Ellwood, C Flohr, S Foliaki, F Forastiere, L García-Marcos, U Keil, CKW Lai, J Mallol, S Montefort, J Odhiambo, N Pearce, CF Robertson, D Strachan, E von Mutius, SK Weiland, G Weinmayr, H Williams, G Wong, TO Clayton, E Ellwood, CE Baena-Cagnani, M Gómez, J Weyler, R Pinto-Vargas, AJLA Cunha, L de Freitas Souza, A Ferguson, L Amareles, P Aguilar, LAV Benavides, A Contreras, Y-Z Chen, O Kunii, Q Li Pan, N-S Zhong, G Wong, AM Cepeda, BN Koffi, C Bustos, M-A Riikjärv, R Sa’aga-Banuve, J Pekkanen, E Vlaski, G Zsigmond, SK Sharma, CB Kartasasmita, P Konthen, W Suprihati, M-R Masjedi, H Odajima, J Kudzyte, M Barragán-Meijueiro, BE Del-Río-Navarro, FJ Linares-Zapién, N Ramírez-Chanona, S Romero-Tapia, Z Bouayad, R MacKay, C Moyes, P Pattemore, BO Onadeko, P Chiarella, A Brêborowicz, G Lis, R Câmara, JM Lopes dos Santos, C Nunes, JE Rosado Pinto, DYT Goh, HJ Zar, H-B Lee, A Blanco-Quirós, RM Busquets, I Carvajal-Urueña, G García-Hernández, C González Díaz, A López-Silvarrey Varela, MM Morales-Suárez-Varela, EG Pérez-Yarza, O Al-Rawas, S Mohammad, Y Mohammad, K Tabbah, J-L Huang, C-C Kao, M Trakultivakorn, P Vichyanond, HH Windom, D Holgado, MC Lapides, D Solé, M Sears, V Aguirre, L Waqatakirewa, J Shah, K Baratawidjaja, S Nishima, M Baeza-Bacab, B-W Lee); E Vlaski (BMJ Publishing Group Ltd., 2014)
Objective: To investigate whether reported fast-food consumption over the previous year is associated with higher childhood or adolescent body mass index (BMI). Design: Secondary analysis from a multicentre, multicountry cross-sectional study (International Study of Asthma and Allergies in Children (ISAAC) Phase Three). Subjects and methods: Parents/guardians of children aged 6–7 completed questionnaires which included questions about their children’s asthma and allergies, fast-food consumption, height and weight. Adolescents aged 13–14 completed the same questionnaire. The questionnaire asked “In the past 12 months, how often on average did you (your child) eat fast-food/burgers?” The responses were infrequent (never/only occasionally), frequent (once/twice a week) or very frequent (three or more times per week). A general linear mixed model was used to determine the association between BMI and fast-food consumption, adjusting for Gross National Income per capita by country, measurement type (whether heights/weights were reported or measured), age and sex. Results: 72 900 children (17 countries) and 199 135 adolescents (36 countries) provided data. Frequent and very frequent fast-food consumption was reported in 23% and 4% of children, and 39% and 13% of adolescents, respectively. Children in the frequent and very frequent groups had a BMI that was 0.15 and 0.22 kg/m2 higher than those in the infrequent group (p<0.001). Male adolescents in the frequent and very frequent groups had a BMI that was 0.14 and 0.28 kg/m2 lower than those in the infrequent group (p<0.001). Female adolescents in the frequent and very frequent groups had a BMI that was 0.19 kg/m2 lower than those in the infrequent group (p<0.001). Conclusions: Reported fast-food consumption is high in childhood and increases in adolescence. Compared with infrequent fast-food consumption, frequent and very frequent consumption is associated with a higher BMI in children. Owing to residual confounding, reverse causation and likely misreporting, the reverse association observed in adolescents should be interpreted with caution.